KORELASI ANTARA STADIUM PADA WAKTU BEROBAT PERTAMA KALI DENGAN ANGKA KEKAMBUHAN PENYAKIT PADA PASIEN KARSINOMA MAMMAE DI RSUP DR. SARDJITO TAHUN 2011 - , Suryanti K Lase, Dr. Kunta Setiadi, Sp. B(K), Onk ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Breast cancer is the second most common malignancy in Indonesia after cervical cancer, and got the first rank in the western or developed world, with high mortality rates, the problems encountered in the treatment of breast cancer, starting with screening, diagnostic, therapeutic and relapse. In general, the life expectancy of patients with breast cancer for 5 years depending on the stage, in the early stages can reach 80%, while in the case of advanced or metastatic only reached 20%. In general recurrence of breast cancer can be caused by various factors, individual factors, including age, pre / post menopause